1995
DOI: 10.1144/gsl.sp.1995.089.01.08
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP zircon age control of Gondwanan sequences in Late Carboniferous and Early Permian Australia

Abstract: Australia during the Late Carboniferous formed part of the Gondwana supercontinent and was close to the South Pole. Resulting continental glacigene deposits and cold water marine sequences in the Southern New England Orogen cannot be correlated biostratigraphically with Late Carboniferous successions in the northern hemisphere because they contain a low diversity biota endemic to Gondwana. Magnetostratigraphic correlation via the Permian-Carboniferous reversed magnetic superchron is presently uncertain. Sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 30 publications
6
65
0
1
Order By: Relevance
“…These provinces may have changed compositionally over time within the Carboniferous as indicated by mid-Carboniferous floras on Gondwana that were referred to as the Paracas flora (Alleman & Pfefferkorn 1988, Pfefferkorn & Alleman 1989, Iannuzzi et al 1998. The tropical coal belt appears to have developed during the Namurian A (Pendleian), during the late Early Carboniferous (Raymond 1996), probably in response to the onset of glaciation (Roberts et al 1995). Raymond (1996) argued that glaciation increased global biogeographic differentiation by establishing and maintaining an ever-wet, ever-warm equatorial climate and by steepening the equator-to-pole temperature and rainfall gradient.…”
Section: Carboniferous and Permian Vegetationmentioning
confidence: 99%
“…These provinces may have changed compositionally over time within the Carboniferous as indicated by mid-Carboniferous floras on Gondwana that were referred to as the Paracas flora (Alleman & Pfefferkorn 1988, Pfefferkorn & Alleman 1989, Iannuzzi et al 1998. The tropical coal belt appears to have developed during the Namurian A (Pendleian), during the late Early Carboniferous (Raymond 1996), probably in response to the onset of glaciation (Roberts et al 1995). Raymond (1996) argued that glaciation increased global biogeographic differentiation by establishing and maintaining an ever-wet, ever-warm equatorial climate and by steepening the equator-to-pole temperature and rainfall gradient.…”
Section: Carboniferous and Permian Vegetationmentioning
confidence: 99%
“…Highprecision dating of multiple volcanic tuffs in these sequences now provides a robust highresolution temporal framework that can be globally correlated and can thus provide vital constraints on the nature of biotic crises, climate change and other geological events. We here present twenty-eight new high-precision U-Pb zircon CA-TIMS dates for P-T air-fall tuffs in the Sydney and Bowen Basins of eastern Australian Gondwana that provide vital undertake an innovative program of tuff dating to address this problem (Roberts et al, 1995a(Roberts et al, , 1995b(Roberts et al, , 1996. The results from these studies were controversial as they contradicted previously assigned ages based on biostratigraphy and in some cases indicated that rocks regarded as Permian were in fact Triassic (Draper et al, 1997).…”
mentioning
confidence: 99%
“…2009);33, Newell (1958); 34, Dickins et al (1989), Archbold et al (1996); 35, Archbold et al (1996); 36, Wanner (1940), Archbold et al (1996). Ages for glacial periods: in Argentina, according to González (1981González ( , 1990González ( , 2002 and González & Díaz-Saravia (2007); in Australia, to Roberts et al (1995), Dickins (1996) and Fielding et al (2008a, b); in Brazil, to Holz et al (2008); in India, to Veevers & Tewari (1995) and Maejima et al (2001). Ages for Biozones in Argentina and Australia from Kelly et al (2001); for Marginirugus barringtonensis, Roberts et al (1976 Oriocrassatella sp.…”
Section: Oriocrassatella In Space and Timementioning
confidence: 98%
“…This warming eliminated the climatic barrier that interrupted the faunal interchange during the "Middle" Carboniferous glacial period and favored larval dispersion following a South to The Late Pennsylvanian time elapsed without records of Oriocrassatella (and the Gondwana fauna), except for occurrences in Argentina (see Fig. 1[6-8]), may be related to the generalized marine regressions in Gondwana (see Roberts et al 1995;Dickins 1996). In addition, the pattern of occurrences described above for the Late Pennsylvanian may be a result of taphonomic bias and/or incomplete sampling.…”
Section: Summary and Final Remarksmentioning
confidence: 99%